Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/ajh/hpaa123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clock Genes Related to Hypertension in Kidney From Spontaneously Hypertensive Rats

Abstract: Background There is a diurnal variation in the blood pressure fluctuation of hypertension, and blood pressure fluctuation abnormality is considered to be an independent risk factor for organ damage including cardiovascular complications. In the current study, we tried to identify molecules responsible for blood pressure circadian rhythm formation under the control of the kidney biological clock in hypertension. Methods DNA mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…On the other hand, disrupted circadian clocks are also closely correlated with MetS components and glucose homeostasis. Recent in vivo studies indicate that peripheral clocks dysregulations in the liver, adipose, kidney, and smooth muscles are involved in the development of hypertension, diabetes, and obesity ( Chang et al, 2018 ; Nakashima et al, 2018 ; Hou et al, 2019 ; Murata et al, 2020 ; Pati et al, 2021 ). In Dec1-deficient mice models, expression of Atp1b1, a negative transcriptional target of Dec1 and anti‐phase regulator of blood pressure rhythm, was upregulated in the kidney, aorta, and heart tissues, and in turn reduced blood pressure ( Nakashima et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, disrupted circadian clocks are also closely correlated with MetS components and glucose homeostasis. Recent in vivo studies indicate that peripheral clocks dysregulations in the liver, adipose, kidney, and smooth muscles are involved in the development of hypertension, diabetes, and obesity ( Chang et al, 2018 ; Nakashima et al, 2018 ; Hou et al, 2019 ; Murata et al, 2020 ; Pati et al, 2021 ). In Dec1-deficient mice models, expression of Atp1b1, a negative transcriptional target of Dec1 and anti‐phase regulator of blood pressure rhythm, was upregulated in the kidney, aorta, and heart tissues, and in turn reduced blood pressure ( Nakashima et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the nuclear factor E4BP4 repress DBP binding to D-box, inhibiting the expression of CCGs, forming the third stabilizing loop [39]. Deficiency or alteration of any of the components of the core circadian clock has an enormous impact at the vascular level, causing atherosclerosis [37][38][39] and risk of thrombosis [53], alteration of blood hemodynamics [43][44][45][46][47], promoting vascular injury [48], and contributes to aging [49][50][51][52]. It also alters liver function [40][41][42].…”
Section: Circadian Rhythm: Clock Components and Vascular Involvementmentioning
confidence: 99%
“…Deficiency in BMAL1 or PER2 is characterized by an increased vasoconstrictor response mediated by cyclooxygenase-1 (COX1) and reduced vasorelaxation mediated by decreases in NO and prostaglandin production [51,52]. All these factors increase the risk of hypertension in animal models [53]. The effects of BMAL1 deficiency are cell-type dependent; blood pressure rhythmicity is unaffected by deletion of Bmal1 in mouse cardiomyocytes, but is disrupted by deletion in vascular smooth muscle cells or endothelial cells [65].…”
Section: Circadian Rhythm: Clock Components and Vascular Involvementmentioning
confidence: 99%
“…The authors reported that Rev-Erbα/β inhibition reduced folic-acid-induced inflammatory cytokine (TNFα, IL-1β) secretion, renal injury (KIM-1 and NGAL), and profibrotic (TGF-β, αMSA) gene expression [ 112 ]. Rev-Erbα expression was increased in the renal cortex and medulla of spontaneously hypertensive rats (SHRs) and stroke-prone SHR rats (SHRSP), compared to normal Wistar rats [ 202 ]. Dexamethasone administration to tubular epithelial cells of mice increased Rev-Erbα , Fragile X mental retardation autosomal homolog 1 ( Fxr1 ), and phosphoribosyl pyrophosphate amidotransferase ( Ppat ) expression [ 202 , 203 ].…”
Section: Effect Of Rev-erb In Tissue Fibrosismentioning
confidence: 99%
“…Rev-Erbα expression was increased in the renal cortex and medulla of spontaneously hypertensive rats (SHRs) and stroke-prone SHR rats (SHRSP), compared to normal Wistar rats [ 202 ]. Dexamethasone administration to tubular epithelial cells of mice increased Rev-Erbα , Fragile X mental retardation autosomal homolog 1 ( Fxr1 ), and phosphoribosyl pyrophosphate amidotransferase ( Ppat ) expression [ 202 , 203 ]. Fxr1 and Ppat are involved in the formation of circadian rhythm in kidney tubules [ 202 ].…”
Section: Effect Of Rev-erb In Tissue Fibrosismentioning
confidence: 99%